Competing core and single particle excitations in the 2$_1^+$ state in $^{44}$Ca - Taylor, M.J.; Benczer-Koller, N.; Kumbartzki, G.; Mertzimekis, T. J.; Robinson, S.J.Q.; Sharon, Y. Y.; Zamick, L.; Stuchbery, A.E.; Hutter, C.; Beausang, C.W.; Ressler, J.J.; Caprio, M.A. (Phys. Lett. B, 2003)
The g factor of the 21+ state in 44Ca has been measured using the transient field technique and Coulomb excitation in inverse kinematics. A positive value of g(21+, 44Ca) = +0.12±0.05 was deduced. The result suggests the (fp)v4 configuration competes with excitations of the 40Ca core. A simple model which considers that the wave function for the 21+ state consists of approximately equal admixtures of spherical four valence neutron configurations and a deformed core configuration accounts for the experimentally observed g factor as well as the previously measured quadrupole moment. © 2003 Published by Elsevier Science B.V.
Keywords: 44Ca; article; calcium; calculation; complex formation; Coulomb excitation; g factor; Inverse kinematics; Kinematics; magnetic field; Magnetic moment; magnetism; mathematical analysis; measurement; physics; Transient field